2012
DOI: 10.1097/dcr.0b013e318255ae8a
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of Intersphincteric Fistula Tract

Abstract: Ligation of intersphincteric fistula tract has had excellent success in transsphincteric fistulas in multiple small series. A larger number of patients and longer follow-up period are needed to validate the early favorable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 14 publications
4
49
2
5
Order By: Relevance
“…In contrast, Abcarian et al . demonstrated a trend towards lower success rates as the number of prior attempts at repair by other means increased.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, Abcarian et al . demonstrated a trend towards lower success rates as the number of prior attempts at repair by other means increased.…”
Section: Resultsmentioning
confidence: 98%
“…Success rates range from 57 to 94% with variable follow-up [12][13][14][15] as shown in Table 1. Overall, a pooled cumulative success rate of 74% can be drawn from this worldwide experience.…”
Section: Discussionmentioning
confidence: 99%
“…The initial report in 2006 from Rojanasakul et al [11] showed a 94% healing rate with a 3-month follow-up. Since then, only a few studies of the use of this technique have been reported, mainly published as abstracts, and with variable success rates from 57 to 89% [12][13][14][15]. This intuitive technique is based on the concept of secure closure of the internal opening and concomitant removal of infected cryptoglandular tissue in the intersphincteric plane.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure is based on closure of the internal opening and removal of infected tissue via an intersphincteric approach. In the first small case series, a 94% success rate was reported and these results were confirmed by a pilot study including 40 patients96 97 A recent study showed more moderate success rates (56% healing >1 year) and all recurrences were within 2 months after the surgery 98. Prospective studies with higher numbers of Crohn's patients are further awaited.…”
Section: Consensus Statementsmentioning
confidence: 85%